Hubungan Tingkat Solidaritas, Tingkat Konformitas Terhadap Tindakan Cancel Culture Penggemar K-POP di Indonesia - Evina Cahyani Budiaji (Journal of Development and Social Change, 2024)
This study aims to explain the relationship between the level of solidarity, the level of conformity, and cancel culture actions among K-Pop fans in Indonesia. The theories used in this research are Emile Durkheim's theory of solidarity and Talcott Parsons' structural functionalism theory. The study employs a quantitative approach, survey method, and explanatory research design. Data were collected through online questionnaires from 96 K-Pop fans who follow the X account @starfess (population: 977,853 accounts). Data analysis techniques included data tabulation and correlation statistics tests (product-moment correlation test, partial product-moment correlation, and multiple correlation), assisted by the Statistical Package for the Social Sciences (SPSS) for Windows version 25.0. The results indicate a strong relationship between solidarity and conformity rxz = 0.777, a weak relationship between conformity and cancel culture actions rzy = 0.366, and a weak relationship between solidarity and cancel culture actions rxy = 0.330. The relationship between solidarity and cancel culture actions through conformity among K-Pop fans in Indonesia is rxy.z = 0.078, indicating an impure relationship. Collectively, solidarity, conformity, and cancel culture actions show a low relationship Ry.xz = 0.375. These findings demonstrate that Emile Durkheim's theory of solidarity and Talcott Parsons' structural functionalism theory effectively explain the interconnectedness of these three variables.